The Grammatical Interference of Indonesian Students in Learning English - Aswinda Darwis (Journal of Applied Linguistics, 2023)
Interference is one of many factors that can damage a language system. It frequently happens in langauge learning process. The interference happened due to the tendency to adapt the feature of one language to another without considering the similarities and differences between the languages. Language interference can take part either in phonological, lexical, or grammatical aspects. The current paper aims to reveal the most frequent grammatical interference made by the students in learning English. To get broader insight, the library research is carried out. It relies on other articles under the same concers of students’ grammatical interference in learning English as the main objective. Six researches were taken to be referred as the primary sources which were published within the last 5 years. The results of each study were explored to get more comprehension for the inquiries of this paper. Based on the analysis, the results showed that the students’ grammatical interference in learning English were made in the form of morphological and syntactical structure. The most frequent syntactical interference deals with word order. While the morphological interference was dominated by the use of tense, be form, subject-verb agreement, singular and plural form. Keywords : Grammatical Interference, Indonesian, English Learning